(untitled) (Eurasian Journal of Ecology, 2016)
In the article discused the questions of formation of the suburban areas of Almaty city and the surrounding regions of Almaty agglomeration, also the settlement prediction of breakthrough projects of perspective population: the zone of influence of Almaty city, a suburban area and a special area of urban management. Based on a comprehensive analysis and evaluation of urban areas, perspective planning structure, trends, socio-economic development of suburban areas, the total natural and ecological characteristics of the environment and the main directions of the design decisions of the General Plan of Almaty city identified functional areas.